Green Betel Leaf Gel (Piper betle) as an Alternative to Perineal Wound Healing in Postpartum Mothers - Mayta Tazkiya Amalia (Archives of The Medicine and Case Reports, 2023)
Perineal wounds are tears that occur when the baby is born either spontaneously or by using a tool or action. Administration of amoxicillin and mefenamic acid as pharmacological treatment is not enough for perineal wound healing. An alternative way to heal perineal wounds is using green betel leaf gel, which has the advantage of cold gel properties, so it can reduce pain. The gel has benefits as an anti-inflammatory, antioxidant, antiseptic, and antibacterial, so it can be used as a perineal wound treatment that can help accelerate perineal wound healing. This study aimed to prove the administration of green betel leaf gel (Piper betle) effect on perineal wound healing in postpartum mothers. This study is a quasy experiment with a pretest and posttest with a control group design. Through the technique of purposive sampling, it was found that 32 respondents were divided into two groups, the control group with clean, dry wound care and the intervention group, which was given green betel leaf gel twice a day for 7 days as measured using the REEDA score. Green betel leaf gel is effective for perineal wound healing on the 7th day compared to dry clean treatment.